Effects of plyometric training on volleyball smash performance: A pre-experimental study - Sujarwo; Dilli Kuswoyo (Physical Therapy Journal of Indonesia, 2025)
Background: Volleyball requires explosive leg power and coordination for effective spike performance, yet many adolescent athletes in sports-specialization classes in Indonesia show limited lower-limb power. This study aimed to compare the effects of two plyometric exercises, box jumps and squat jumps, on improving spike performance among these students in Yogyakarta. Methods: Twelve male sports-specialization students participating in extracurricular volleyball were purposively assigned to box jump or squat jump training groups (n = 6 each). Spike performance was assessed using a standardized skill test, and results were analyzed with descriptive statistics and paired-sample t-tests. Results: Both training groups showed improvements in volleyball spike performance. The box jump group increased from a pretest mean of 34 to a posttest mean of 64 spikes (t = 2.19), while the squat jump group improved from 31 to 45 spikes (t = 1.26). Neither change reached statistical significance at α = 0.05 (critical t = 2.571). Numerically, the box jump group showed a larger and more consistent gain than the squat jump group. Conclusion: Plyometric training led to practical improvements in volleyball spike performance, especially in the box jump group, though changes were not statistically significant. These results indicated that plyometric exercises could benefit school-based volleyball programs, while further research with larger samples and longer interventions is needed to confirm their effectiveness.